Hematological parameters of COVID-19 patients at Jakarta Pondok Kopi Islamic Hospital : martelina - lina, martelina (Sanus Medical Journal, 2024)
The 2019 Corona Virus Disease (Covid-19) has become a pandemic. As of 15 January 2021, in Indonesia there were 896,642 confirmed cases and 25,767 deaths. Diagnosis of COVID-19 is based on real-time reverse transcriptase-polymerase chain reaction (RT-PCR) results on oropharyngeal/nasopharyngeal swab samples. A basic hematological examination is also conducted on patients with suspected COVID-19. The purpose of this study is to identify the hematological parameters of COVID-19 patients at Pondok Kopi Islamic Hospital in Jakarta (RSIJ PK) to provide an overview of the hematological parameters that can be used to predict the possibility of a patient being infected with COVID-19